The Efficacy of Nasal Steroids in Treatment of Otitis Media with Effusion: A Comparative Study - El-Anwar,Mohammad Waheed (2015)
Introduction Otitis media with effusion (OME) continues to be an important pediatric clinical problem, and more studies are needed to decide the proper treatment for it. Objective To assess the efficacy of nasal steroids in the management of OME by comparing its results with that of oral steroid and that of nasal saline spray as placebo. Methods This study was carried on 60 patients with OME who were divided into three groups: in group 1, 20 patients received mometasone furoate spray, one puff in each nostril daily, for 3 months; in group 2, 20 patients received oral prednisolone, 5 mg three times per day for the first 3 weeks; in group 3, 20 patients received nasal saline spray, one puff in each nostril daily for 3 months. Results A highly significant difference between systemic or topical (nasal spray) steroid therapy and saline nasal spray was detected (p < 0.001), and the difference between systemic and topical steroid was nonsignificant (p > 0.05). Conclusion Nasal steroid spray can be used as an effective treatment for OME, giving a significant result similar to systemic steroid. Further studies are needed to investigate its use for longer duration and in recurrent cases.